Proportional Assist Ventilation Improves Leg Muscle Reoxygenation After Exercise in Heart Failure With Reduced Ejection Fraction - Borghi-Silva, Audrey; Goulart, Cassia da Luz; Carrascosa, Cláudia R.; Oliveira, Cristino Carneiro; Berton, Danilo C.; de Almeida, Dirceu Rodrigues; Nery, Luiz Eduardo; Arena, Ross; Neder, J. Alberto (Frontiers in Physiology, 2021)
Background: Respiratory muscle unloading through proportional assist ventilation (PAV) may enhance leg oxygen (O2) delivery, thereby speeding off-exercise O2 uptake ( O2) kinetics in patients with heart failure with reduced left ventricular ejection fraction (HFrEF). Methods: Ten patients (HFrEF= 26±9%) underwent two constant-work rate (70-80% peak) tests to tolerance under PAV or sham ventilation. We assessed post-exercise kinetics of the “primary” component of O2, vastus lateralis fractional O2 extraction by near-infrared spectroscopy deoxyhemoglobin ([deoxy-Hb+Mb]) and cardiac output (QT) by impedance cardiography. Results: PAV significantly accelerated O2 recovery when compared with sham (τ = 56±22s vs. 77±42s, respectively, p<0.05). PAV was also associated with a faster decline in ∆[deoxy-Hb+Mb] and QT (τ= 31±19s vs. 42±22s and 39±22s vs. 78±46s, respectively, p<0.05). Faster off-exercise QT with PAV was related to longer exercise duration (r= -0.76; p<0.05). Conclusion: PAV accelerates the recovery of central hemodynamics and muscle oxygenation in HFrEF. These beneficial effects might prove useful to improve the tolerance to repeated exercise during cardiac rehabilitation.